PENGUKURAN KINERJA DATA HUJAN CHIRPS DALAM PENILAIAN KEKERINGAN DI LOMBOK TENGAH - SAIDAH, HUMAIRO; YASA, I WAYAN; SULISTIYONO, HERI (GANEC SWARA, 2024)
Drought index analysis requires long data requirements. However, the complete and long recording periods of rainfall data are still the main obstacles to meeting rainfall data needs. Apart from that, there are still many areas that do not have adequate and evenly distributed rain recording stations. This research aims to see if the use of CHIRPS (Climate Hazard Group Independent Precipitation with Station Data) satellite rainfall data can be used to calculate the drought index using the SPI (Standardized Precipitation Index) method. The research began with collecting rain data from ARR measurements and downloading CHIRPS satellite rain data. CHIRPS data is corrected first by reducing the correction factor using simple regression where CHIPS data is the independent variable and ARR data is the dependent variable. CHIRPS data was then corrected and used in calculating the drought index using the SPI method. The results of the SPI calculation from the corrected CHIRPS rainfall data were then compared with the drought index resulting from analysis using ARR data. The results obtained show that both CHIRPS data and ARR data produce the highest drought index with the Normal severity category. The drought index resulting from CHIRPS data analysis is stated to be quite good and corresponds to a suitability level of 60%. So the CHIRPS data is declared good and can be used for drought analysis in this region.